Properties of patient-reported outcome measures in individuals following acute whiplash injury. - Pink, J; Petrou, S; Williamson, E; Williams, M; Lamb, S (BioMed Central, 2014)
BACKGROUND: The aim of this study was to assess the acceptability, reliability, validity and responsiveness of the Short-Form Health Survey (SF-12) and its preference-based derivative (SF-6D), the EQ-5D and the Neck Disability Index (NDI) in patients recovering from acute whiplash injury. METHODS: Data from the Managing Injuries of the Neck Trial of 3,851 patients with acute whiplash injury formed the basis of this empirical investigation. The EQ-5D and SF-12 were collected at baseline, and all three outcome measures were then collected at 4 months, 8 months and 12 months post-randomisation. The measures were assessed for their acceptability (response rates), internal consistency, validity (known groups validity and discriminant validity) and their internal and external responsiveness. RESULTS: Response rates were broadly similar across the measures, with evidence of a floor effect for the NDI and a ceiling effect for the EQ-5D utility measure. All measures had Cronbach's α statistics of greater than 0.7, indicating acceptable internal consistency. The NDI and EQ-5D utility score correlated more strongly with the physical component scale of the SF-12 than the mental component scale, whilst this was reversed for the SF-6D utility score. The smaller standard deviations in SF-6D utility scores meant there were larger effect sizes for differences in utility score between patients with different injury severity at baseline than for the EQ-5D utility measure. However, the EQ-5D utility measure and NDI were both more responsive to longitudinal changes in health status than the SF-6D. CONCLUSIONS: There was no evidence of differences between the EQ-5D utility measure and NDI in terms of their construct validity, discriminant validity or responsiveness in patients with acute whiplash injury. However, both demonstrated superior responsiveness to longitudinal health changes than the SF-6D.